PENGARUH VARIASI GEOGRAFIS TERHADAP WAKTU MATAHARI TERBENAM DAN SYAFAQ: STUDI KOMPARATIF DI PANTAI KURI DAN KECAMATAN CAMBA, KABUPATEN MAROS - Gibran, Muh. Chalil; Agus, Jasdar (HISABUNA: Jurnal Ilmu Falak, 2026)
Abstract The determination of prayer times, especially Maghrib and Isha, is highly dependent on the astronomical phenomena of sunset and the disappearance of twilight (syafaq). Variations in geographical conditions such as altitude and horizon characteristics can potentially cause time differences, yet systematic comparative studies in areas with contrasting topography remain limited. This study aims to: 1) analyze the results of hisab calculations for sunset and syafaq disappearance in the mountainous area (Camba District) and coastal area (Kuri Beach), Maros Regency, and 2) examine the influence of geographical differences and altitude on these two times. This research employs a quantitative approach with a descriptive-comparative method based on astronomy (hisab). Geographical data were obtained via Google Earth, while solar astronomical data (declination and equation of time) were sourced from the 2026 Ephemeris of the Ministry of Religious Affairs of the Republic of Indonesia. Calculation samples were taken on four dates representing seasonal changes: March 1, June 1, September 1, and December 1, 2026. The results show that the coastal area of Kuri Beach (±5 masl) consistently experiences later Maghrib and Isha times compared to the mountainous area of Camba (±480 masl), with a time difference ranging from 1 to 2 minutes. Scientifically, this difference is caused by the influence of elevation on the geometric horizon and local horizon conditions. Although the difference is small, from a Sharia perspective, it is significant as it relates to the validity of worship, particularly in the context of hastening to break the fast. This study concludes that geographical factors and altitude have a real influence on determining prayer times; thus, the concept of ihtiyath (precautionary time) is crucial in preparing prayer schedules to accommodate local variations.